'Boat People' and Discursive Bordering: Australian Parliamentary Discourses on Asylum Seekers, 1977-2013 - van Kooy, John; Magee, Liam; Robertson, Shanthi (Refuge, 2021)
This article draws upon content analysis of Australian parliamentary transcripts to examine debates about asylum seekers who arrived by boat in three historical periods: 1977–1979, 1999–2001, and 2011–2013. We analyze term frequency and co-occurrence to identify patterns in specific usage of the phrase “boat people.” We then identify how the term is variously deployed in Parliament and discuss the relationship between these uses and government policy and practice. We conclude that forms of “discursive bordering” have amplified representations of asylum seekers as security threats to be controlled within and outside Australia’s sovereign territory. The scope of policy or legislative responses to boat arrivals is limited by a poverty of political language, thus corroborating recent conceptual arguments about the securitization and extra-territorialization of the contemporary border.